1997
DOI: 10.1007/bf03160715
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic indices for nontidal wetlands

Abstract: Two sets of hydrologic indices were developed to characterize the water-budget components of nontidal wetlands. The first set consisted of six water-budget indices for input and output variables, and the second set consisted of two hydrologic interaction indices derived from the water-budget indices. The indices then were applied to 19 wetlands with previously published water-budget data. Two trilinear diagrams for each wetland were constructed, one for the three input indices and another for the three output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…For example, Lent et al (1997) summarize water budgets for 19 well-characterized wetlands that show a nearly complete continuum among sources of water. Wetlands resulting from water con L tributed by only precipitation and runoff would not be revealed by the model.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…For example, Lent et al (1997) summarize water budgets for 19 well-characterized wetlands that show a nearly complete continuum among sources of water. Wetlands resulting from water con L tributed by only precipitation and runoff would not be revealed by the model.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…DOC fluxes summarized by Jordan et al (1983) were also reviewed in Taylor and Allanson (1995 Implications for pore-water flushing and wetland-estuary exchange-The flux of water governs the exchange of materials in and out of wetlands. Consequently, Lent et al (1997) suggested that the dominance of different components of water balances defines the degree of wetland interaction within the landscape. The Ringfield marsh was thus more hydrologically isolated within the landscape in the late summer (July and August) when precipitation and evapotranspiration were a greater proportion of the sediment water budget.…”
Section: Discussionmentioning
confidence: 99%
“…It quantifies what Brinson (1993a) presented as a ternary diagram showing the relative importance only of water inputs. Combining the proportions of both inputs and outputs, Lent et al (1997) derived 9 basic hydrologic types of wetlands. Interestingly, "types" based on vegetation (e.g., marshes, swamps, bogs, fens) did not all group together into single hydrologic "types.…”
Section: A Diversity Of Biological and Functional Templatesmentioning
confidence: 99%
“…These indices provide quantitative indications of the strength and type of water exchanges between a wetland and the larger ground-water and surface-water systems of which it is a part (Lent et al 1997). These indices quantify the hydrologic portion of what Brinson (1993a) presented as conceptual categories (e.g., donor, receptor, conveyor) for classifying wetlands according to exchanges of elements and sediments as these are affected by water exchanges.…”
Section: A Diversity Of Biological and Functional Templatesmentioning
confidence: 99%
See 1 more Smart Citation